(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, the exact solution of one-dimensional isentropic Euler equations is studied. When the exponent of the state equation satisfies γ = 2, we get an exact solution which is linear with respect to the spatial variable x. For this end, we solve some ordinary differential equations with time dependent variable coefficients.